Perception of Architecture Students on Factors Influencing the Selection of Locations for Academic Trip and Site Visit - Mohammad Yusoff, Wardah Fatimah; Ja'afar, Nor Haslina; Mohammad, Noraziah (Journal of Technical Education and Training, 2019)
One of the approaches in the architectural design studio pedagogy is an academic trip, in which it is always associated with a site visit. This approach is widely applied in architectural education around the world. However, there are challenges in executing this approach. Thus, this study aims to identify the students' perceptions of the academic trip and site visit via factors that influence the trip location. A mixed-method approach was applied, where it involved 32 questionnaire surveys and 20 in-depth interviews. The final year Bachelor of Science in Architecture students of Universiti Kebangsaan Malaysia were selected as respondents. The quantitative data from the survey had been analyzed using simple statistic such as percentage and frequency. However, the qualitative data gained from the in-depth interview was analyzed using thematic analysis. The findings indicate that the students opine that the visit is beneficial for them. However, most of them also agree that the factors of travelling time, financial and knowledge exposure affect their choices for the location. The findings also demonstrate that the students still opt for farther academic trip and site visit location though they face financial issues. Hence, it is recommended that further action should be taken such as the provision of financial support to encourage the academic trip and site visit as the architectural design studio pedagogies. Farther location of the visit provides more exposure to the students. This helps to produce graduate architects that are more sensitive towards the diversity of culture, heritage and built environment.